Fructose ingestion modifies NMDA receptors and exacerbates the seizures induced by kainic acid. (16th February 2022) - Sánchez-Hernández, Josué; Aguilera, Penélope; Manjarrez-Marmolejo, Joaquín; Franco-Pérez, Javier
Highlights: Fructose decreased the expression of the NR1 subunit and increased the NR2A subunit. Fructose increased the phosphorylation of kinases (PKCα and c-Src) related to NMDA activation. Fructose ingestion exacerbates the seizures induced by kainic acid. Abstract: Fructose ingestion elicits a diversity of brain alterations, but it is unknown how it affects N-methyl-D-Aspartate receptors (NMDAr). Here, we analyzed the expression of NMDAr subunits and protein kinases after the long-term dietary fructose intake. Since NMDAr are related to epileptogenesis, we also examined whether fructose increases the susceptibility to seizures after the microinjection of kainic acid (KA) in the rat hippocampus. Wistar rats were randomly divided into water (control) and fructose groups. For twelve weeks, groups had ad libitum access to water or fructose solution (10% w/v). After treatment, hippocampal protein expression of NMDAr subunits and protein kinases involved in NMDAr regulation were analyzed. Additionally, electroencephalographic and behavioral changes related to seizures were evaluated after the microinjection of a sub-convulsive dose of KA in the hippocampus. Fructose induced the decrease of NR1 and, conversely, the increase of NR2A subunits expression in the hippocampus. Also, the phosphorylation of protein kinase C alpha (PKCα) and c-Src increased significantly. No electroencephalographic or behavioral patterns related to convulsive motor seizures were observed in the control group. However, all the rats that ingested fructose showed stage 3 seizures (forelimb clonus) and a significant increase in the number of wet-dog shakes. Moreover, electroencephalographic recordings revealed pronounced epileptiform activity and increased total spectral power at 30 and 60 min after the microinjection of KA. This study shows for the first time that fructose intake exacerbates the seizures induced by KA. Therefore, we propose that this proconvulsant effect could be mediated by changes in NMDAr subunits expression and increased activation of kinases modulating NMDAr function.